Global sustainable livestock investment overview - Wollenberg, Eva Karoline (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Presented by Lini Wollenberg, CCAFS, on 28 June 2021 at the Asian Development Bank (ADB) Webinar on Sustainable Protein Case Study: Outputs and Synthesis of Results.